Nutritional and functional properties of popped chickpea and red kidney bean - Godrich, Joseph (2024)
The aim of this PhD thesis was to maximise the nutritional and sensory potential of pulses using an underexplored form of high temperature, short time processing called compression popping. Chickpea and red kidney bean, which are known to contain ample quantities of nutrients but also antinutritional factors, were compression popped prior to nutritional analysis. Research was conducted to see if high temperature and pressure treatment could sufficiently reduce antinutritional factors and enhance nutrient digestibility and bioavailability, increasing the nutritional value of pulses as a form of food or food ingredient.